The impact of covid-19 pandemic on emergency services - Muselli, M.; Cofini, V.; Mammarella, L.; Carmignani, C.; Fabiani, L.; Desideri, G.; Necozione, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The SARS-Cov-2 pandemic has placed enormous strain on the global healthcare system. The strict containment measures have adversely affected population movements and mobility, daily activities, and the patterns of healthcare-seeking behavior. Although the Emergency and Admission Departments (EADS) activity has never been disrupted, the pandemic had a significant impact on the routine healthcare delivery. This study aims to assess the changes in healthcare delivery, with a focus on the elderly as a vulnerable component of the general population. Design of the study. Retrospective study.Methods. All non-COVID visits to the EAD of the Local Health Unit (ASL1) in Abruzzo (Italy) from 9 March to 3 May 2020 were analyzed. These were compared to the hospital admissions recorded in the same period of the previous year.Results. We found a 60.4% reduction in overall visits during the study period and an increase in the hospitalization rate from 30% to 39%. Emergency department visits have declined markedly for less acute medical conditions, while we have observed a statistically significant increase in the hospitalization rates for all age groups. Moreover, in 2020 we recorded a decrease in the ratio non-urgent/non-deferrable medical conditions for each age group; while the percentage of hospitalizations for each registered red code increased for each group, particularly for the 65-74 age group.Conclusions. The COVID-19 pandemic has significantly affected the care-seeking behavior of patients. During the COVID-19 epidemic, total hospital admissions have decreased, particularly for less severe illnesses, whereas the percentage of hospitalizations has increased. During 2020, hospital admissions for mild cases decreased, and patients presented to the EAD only in cases of acute medical condition, selecting those in need for more intensive care. However, several patients may have deferred necessary medical care even for potentially urgent conditions. Such reluctance to seek medical care may have caused delays in diagnosis. The impact of deferred care on patients’ health is difficult to estimate at this time. This information will serve as a starting point for further research to improve healthcare management not only during emergency but also in non-emergency periods.